Meningkatkan Pengetahuan Dan Pengelolaan Keuangan Sejak Dini Melalui Gerakan “Ayo Menabung” - Falikhah, Anis Nala; Putriningsih, Saniyah; Erininda , Wafika; Adinugraha, Hendri Hermawan; Shulthoni, Muhammad (Welfare : Jurnal Pengabdian Masyarakat, 2025)
This service highlights the urgency of financial literacy among children in Denasri Wetan Village, facing the era of globalization. Financial literacy education is introduced early to equip children to manage finances effectively in the future. The object of service is elementary school children, especially those who attend Bimbel at Bimbel Asih in Denasri Wetan Village. The "Ayo Menabung" movement is promoted as an innovative solution to improve financial understanding and instill the value of saving. The service method involved counseling and introducing the concept of the "Let's Save" movement through lectures and games. The results of the activity showed a positive impact on children's understanding, with the question and answer session reflecting interest and better understanding. Despite obstacles such as the inattention of some participants, success was measured by positive responses, improved understanding, and active participation. For future activities, it is worth considering improvements such as more appropriate timing and adjustments to delivery methods to increase interactivity. Overall, this service successfully provided financial education to elementary school children, contributing to improving financial literacy in Denasri Wetan Village.